Role of in vivo reflectance confocal microscopy in the diagnosis of scalp psoriasis - Si-ying XIONG; Wei-yu LIU; Wei LI; -xin TIAN; Yu-mei LIU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2019)
Objective: To investigate the imaging features of reflectance confocal microscopy (RCM) in patients with scalp psoriasis, and to analyze the clinical significance of RCM in the diagnosis of scalp psoriasis. Methods: Total 55 patients with scalp psoriasis were enrolled, with RCM scan and histopathological examination were performed respectively. Results: For scalp psoriasis, the significant features were parakeratosis, Munro-micro-abscess, multiple and enlarged dermal papillae, which arrange regularly, and the blood vessels in dermal papillae were dilated and congested. Compared with the histopathology diagnosis, the sensitivity rate, the specific rate, the accuracy rate, the misdiagnosis rate, the missed diagnosis rate, the Youden index and the Kappa value of RCM in diagnosis of scaple psoriasis were respectively 91.8%, 66.7%, 89.1%, 33.3%, 8.2%, 0.585 and 0.510 (P<0.05). Conclusion: RCM scan not only plays an auxiliary role in the diagnosis of scalp psoriasis but also provides clues for differential diagnosis.